2021
DOI: 10.1177/15248380211013132
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Adverse Childhood Experiences and Trauma Among Young People Who Offend: A Systematic Literature Review

Abstract: This systematic review synthesized current knowledge about the prevalence of adverse childhood experiences (ACEs) among young people known to have offended and examined evidence of associations between ACEs, trauma symptoms, and offending behavior. A systematic search of English-language, peer-reviewed studies published from the year 2000 onwards was conducted. A final pool of 124 studies that reported quantitative data were included in the review. The Cambridge Quality Checklist for the assessment of studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 150 publications
4
39
0
1
Order By: Relevance
“…Adverse childhood experiences are an emerging research paradigm in criminology and criminal justice [ 7 , 11 , 12 , 27 , 28 ], but research findings often have a mechanistic dose–response connotation and generally lack specificity. This is unfortunate, as although there is universal acknowledgement that childhood abuse and neglect are destructive and contribute to antisocial development and psychiatric morbidity, granular research findings can inform interventions to treat and supervise adolescents involved with the justice system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adverse childhood experiences are an emerging research paradigm in criminology and criminal justice [ 7 , 11 , 12 , 27 , 28 ], but research findings often have a mechanistic dose–response connotation and generally lack specificity. This is unfortunate, as although there is universal acknowledgement that childhood abuse and neglect are destructive and contribute to antisocial development and psychiatric morbidity, granular research findings can inform interventions to treat and supervise adolescents involved with the justice system.…”
Section: Discussionmentioning
confidence: 99%
“…For example, divorce or parental separation is among the most common forms of adversity, with about 80% of justice system involved youth experiencing it. In contrast, about 12% of justice system involved youth were sexually abused [ 27 ]. In this regard, parental separation is normative, whereas sexual abuse is pathological in statistical terms, and in terms of the broader psychological and behavioral morbidity it sets into motion [ 34 , 35 , 36 , 37 , 38 ], sexual abuse is incomparable as a form of adversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the p Factor spurred research surrounding the conceptualization and measurement of global psychopathology, its salience to criminology is limited and there are several research gaps. For instance, although the p Factor is highly heritable (To illustrate, the authors [ 9 ] analyzed twin data from the Twins Early Development Study and reported that 50% to 60% of variance in the p Factor is attributable to genetic factors and between 49% to 78% of the shared variance in continuity of psychopathology across childhood and adolescence was also owed to genetic factors), the environment also plays a critical role in its development, thus a focus on the rearing environments of criminal offenders, where disparate forms of abuse and neglect are commonplace [ 20 , 21 , 22 , 23 ] is needed. The original p Factor study eschewed low prevalence phenomena that although rare in the general population, are much more prevalent among the correctional population.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is limited empirical evidence to demonstrate causal associations between ACEs, trauma and offending. In fact, a recent systematic review by Malvaso et al (2021) concluded that, although up to 90 percent of justice-involved young people will report exposure to traumatic events, the pooled mean score across 40 studies that specifically assessed post-traumatic stress disorder (PTSD) shows that, on average, these young people will fall short of the diagnostic cut-off for mild PTSD. It is apparent that not every young person who experiences adversity will be 'traumatised' and that not all of those who experience trauma symptomatology will go on to offend.…”
mentioning
confidence: 99%